Effect of aluminum hydroxide (ATH) on flame retardancy and smoke suppression properties of SBS-modified asphalt. Issue 1 (2nd January 2023) - Yang, Xiaolong; Wang, Guangchen; Liang, Mingmei; Yuan, Taiping; Rong, Hongliu
Abstract : In this study, ATH-modified asphalt of different compositions (0wt%, 5wt%, 10wt%, 15wt%, and 20wt%) were prepared for testing. Its flame-retardant performance and dynamic smoke release characteristics were investigated by using the limiting oxygen index (LOI) test and TG-FTIR technology. After pyrolysis, the carbon layer's structure, morphology, and element distribution were analyzed by scanning electron microscopy-energy disperse spectroscopy (SEM-EDS). Adding ATH increased the LOI value of the base asphalt by up to 23.1%. The TG-FTIR results showed that ATH significantly improved the flame-retardant performance of asphalt through three physical effects: cooling, dilution, and heat insulation. Adding ATH to asphalt affected adsorption and blocking, thus reducing smoke, promoting carbon formation, and improving its smoke suppression. Observations of the microscopic carbon layer showed that incorporating ATH improved the integrity and strength of its structure. Based on these results, a mechanistic model of the flame retardancy and smoke suppression of ATH-modified asphalt was established.